FINTECH PAYMENT, FINANCIAL SELF-EFFICACY DAN KEMAMPUAN AKADEMIK TERHADAP PENGELOLAAN KEUANGAN MAHASISWA SARJANA AKUNTANSI - Icha Dwi Rahayu; Kholidiah Kholidiah (Jurnal Ilmiah Akuntansi, 2026)
This study aims to examine the influence of Fintech Payment, Financial Self-Efficacy, and Academic Ability on the Financial Management of Accounting Undergraduate Students at Wijaya Kusuma University Surabaya. Using a quantitative approach, data was collected thru questionnaires from 128 students from the 2022 and 2023 cohorts who had completed the financial management course. The data analysis technique used is multiple linear regression thru SPSS 23 software. Based on the research results, it can be partially known that the variables of financial self-efficacy and academic ability have a positive effect on financial management among accounting undergraduate students at Wijaya Kusuma University Surabaya. Meanwhile, the fintech payment variable does not affect financial management among accounting undergraduate students at Wijaya Kusuma University Surabaya. The research findings conclude that accounting students' financial management is significantly driven by internal factors such as self-confidence (financial self-efficacy) and academic ability, but is not influenced by the use of digital payment technology (fintech payment).